TRANSFORMACJA A PERSPEKTYWY ROZWOJU GOSPODARCZEGO POLSKI - Sadowski, Zdzisław (Wydział Prawa i Administracji UAM, 2009)
Although the systemic transformation in Poland was successful with regard to the basic elements of economic and political change, it also caused some overtly negative phenomena both in the structure of the economy and in its social aspects. In particular, it created great social inequalities, widespread poverty as mass and presistent unemployment. Responsibility is largely attributable to the fact that an important part in shaping economic policies of transition was played by the neoliberal doctrine known to disregard the social costs of economic change. It is clear that in future the successfully re-established market system must be maintained. It will, however, be necessary for the state to play an active role of a co-regulator o f the economy, responsible for supporting the market in its positive functions and applying corrective measures where needed, particularly in respect o f income distribution. The present global economic crisis makes it difficult to discuss Poland’s development prospects, but two issues are considered top priorities: combating poverty and developing an information society with knowledge-based economy. In building the needed institutional set-up it should be useful to apply a modernised concept of the social market economy.
TRANSFORMATION AND ECONOMIC PROSPECTS FOR POLAND